Frankenstein - Shelley M. Mary (Newbury, Express Publishing, 2000)
This edition unites the dark side of Barry Mosers art with the classic 1818 text of Mary Shelleys tale of moral transfiguration. In a vivid sequence of woodcuts, the reader witnesses the birth of the monster as Moser shapes him from darkness. Tells the story of a monstrous creation.